Water Uptake from Different Soil Depths for Desert Plants in Saline Lands of Dunhuang, NW China - Cui, Yong-Qin; Niu, Li-Qin; Xiang, Jin-Li; Sun, Jia-Huan; Xiao, Jian-Hua; Ma, Jian-Ying (Frontiers in Environmental Science, 2021)
Salinization is a major threat to the sustainability of land and water resources, especially in arid and semiarid regions. Understanding the water uptake from different soil depths for desert plants is useful for exploring salinity-tolerance mechanism in desert plants in extremely-arid and salinity-affected area. To understand water uptake from different soil depths for desert plants in Dunhuang, NW China, we used oxygen isotope composition in plant xylem water and soil water to determine the water sources in three different saline sites differing in their degree of soil electrical conductance (site 2 < site 1 < site 3). The co-existing desert plants in each saline site extracted different depth of soil water respectively: K. foliatum mainly used shallow soil water (0-20 cm); H. caspica and N. tangutorum mainly used deep soil water (40-200 cm); A. sparsifolia used water from the 120-200 cm soil layers, while T. ramosissima and E. angustifolia mainly extracted deeper soil water (> 200 cm). Compared to that in saline site 2, Tamarix ramosissima and Alhagi sparsifolia can switch their water sources to deeper soil water when enduring more salt stress. Also, a significant and positive correlation between soil EC and soil water δ18O values was observed, indicating the evaporation would cause increase in salt concentration and isotopic enrichment in the upper soil profile. Overall, our results suggest that plants may explore deeper soil water to adapt to salt stress under severe salinity. This work may contribute to selecting salt-tolerant plants species which is vital to saline soil rehabilitation and utilization.